The true story of the HD-Zip family - Ariel, Federico Damian (2007)
The HD-Zip family of transcription factors is unique to the plant kingdom. These proteins exhibit the singular combination of a homeodomain with a leucine zipper acting as a dimerization motif. They can be classified into four subfamilies, according to a set of distinctive features that include DNA-binding specificities, gene structures, additional common motifs and physiological functions. Some HD-Zip proteins participate in organ and vascular development or meristem maintenance. Others mediate the action of hormones or are involved in responses to environmental conditions. Here, we review recent data for this family of transcription factors from a wide variety of plant species to unravel their crucial role in plant development.